Entrepreneurial Literacy, Technology Adoption, and MSME Business Success - Muhammad Haidar Nurwaskita (GLOBAL SCIENTS PUBLISHER, 2026)
This study examines the effect of entrepreneurial literacy and technology adoption on the business success of novice entrepreneurs in micro, small, and medium enterprises (MSMEs) in Bogor City. The research was motivated by the role of MSMEs in local economic development and the challenges faced by novice entrepreneurs in business planning, technology utilization, sales growth, profit stability, and customer retention. This study used a quantitative approach with a survey method. The population consisted of 800 novice MSME entrepreneurs, and 107 respondents were selected using the Slovin formula with a 9% margin of error. Data were collected using questionnaires and analyzed through validity and reliability tests, descriptive analysis, classical assumption tests, multiple linear regression, correlation, determination, t-test, and F-test. The results show that entrepreneurial literacy has a positive and significant effect on business success. Technology adoption also has a positive and significant effect on business success and has a more dominant coefficient. Simultaneously, both variables significantly influence business success with an R Square value of 0.420. These findings indicate that improving entrepreneurial knowledge and optimizing digital technology use can strengthen novice entrepreneurs’ business performance.